The effects of Momordica charantia on the liver in streptozotocin-induced diabetes in neonatal rats - Abdollahi, Maryam; Abu Bakar @ Zakaria, Md Zuki; Goh, Yong Meng; Rezaeizadeh, Alireza; Mohamed Mustapha, Noordin (Academic Journals, 2010)
The aim of this study is to determine the effects of Momordica charantia (MC) fruit aqueous extract on the liver histopathological changes in neonatal rats streptozotocin (STZ)-induced diabetes mellitus type II. Diabetes mellitus was induced in one day old neonatal Sprague-Dawley rats with STZ (85 mg/kg) and monitored for 12 weeks thereafter. The diabetic rats were separated into three groups as follows: the diabetic control group (nSTZ), the MC treated diabetic group (nSTZ/M), and the glibenclamide treated diabetic group (nSTZ/G). At the end of the treatment, blood glucose, serum insulin, alanine amino transferases (ALT) and aspartate amino transferases (AST) level was measured. Malondialdehyde (MDA) concentration was measured in the plasma and liver. The liver samples were processed for light microscopy examination. The results showed a reduction of blood glucose, ALT and AST, and increment of insulin level in the nSTZ/M and nSTZ/G rats. Administration of MC reduced the MDA concentration in plasma and liver of the nSTZ/M rats. Glucose tolerance and insulin sensitivity was improved in the nSTZ/M and nSTZ/G groups. The degenerative changes in liver were alleviated in the nSTZ/M and nSTZ/G groups. These results suggested that MC fruit aqueous extract may have a significant role in alleviating liver damage in the nSTZ-diabetic rats.